Nitrogen limitation in arid-subhumid ecosystems: A meta-analysis of fertilization studies - Yahdjian, María Laura (2011)
Evidence supporting water limitation in arid-semiarid ecosystems includes strong correlations between aboveground net primary production (ANPP) and annual precipitation as well as results from experimental water additions. Similarly, there is evidence of N limitation on ANPP in low precipitation ecosystems, but is this a widespread phenomenon? Are all arid-semiarid ecosystems equally limited by nitrogen? Is the response of N fertilization modulated by water availability? We conducted a meta-analysis of ANPP responses to N fertilization across arid to subhumid ecosystems to quantify N limitation, using the effect-size index R which is the ratio of ANPP in fertilized to control plots. Nitrogen addition increased ANPP across all studies by an average of 50%, and nitrogen effects increased significantly (P = 0.03) along the 50-650 mm yr-1 precipitation gradient. The response ratio decreased with mean annual temperature in arid and semiarid ecosystems but was insensitive in subhumid systems. Sown pastures showed significant (P = 0.007) higher responses than natural ecosystems. Neither plant-life form nor chemical form of the applied fertilizer showed significant effects on the primary production response to N addition. Our results showed that nitrogen limitation is a widespread phenomenon in low-precipitation ecosystems and that its importance increases with annual precipitation from arid to subhumid regions. Both water and N availability limit primary production, probably at different times during the year; with frequency of N limitation increasing and frequency of water limitation decreasing as annual precipitation increases. Expected increase N deposition, which could be significant even in arid ecosystems, would increase aboveground net primary production in water-limited ecosystems that account for 40% of the terrestrial surface. © 2011 Elsevier Ltd.